A Systematic Review of Boundary-Crossing Partnerships in Designing Equity-Oriented Special Education Services for Culturally and Linguistically Diverse Students With Disabilities. (December 2021) - Ko, Dosun; Mawene, Dian; Roberts, Kate; Hong, Joan J.
Providing quality special education services for culturally and linguistically diverse (CLD) students with or at risk of disabilities is a double bind, a larger systemic conundrum beyond individuals' efforts. To create an inclusive, culturally responsive system of support beyond the fragmented division of roles and nonconcerted assemblage of practices and tools, there is a need to explore the possibility of boundary-crossing collaboration for CLD students with disabilities. The purpose of this systematic review is to synthesize the broader literature investigating K-12 school-based boundary-crossing collaborations among multiple stakeholders to address the unique academic, social-emotional, and behavioral needs of CLD students with or at risk of disabilities. Eight studies met the criteria for inclusion. Features of boundary crossers, problems of practice that boundary crossers collaboratively sought to address, emerging tensions in building partnership, facilitators of boundary-crossing communication and collaboration, learning experiences of boundary crossers, and learning outcomes of CLD students with or at risk of disabilities are reported and further discussed.